Phenomenology as a method of understanding the meanings of life, part 2 - Kubarev V.S. (Консультативная психология и психотерапия, 2013)
The article identified the main phenomenological features of text: doubling of reality and generation of meaning. In their framework reveals the content side of personal reflection. А distinction is made between two dimensions of phenomenological consciousness "in itself for myself" and "I am for another." The situation of psychotherapeutic dialogue is analyzed in this context. Psychotherapeutic dialogue is seen as a reflexive structure. In conclusion, the article gives the content characteristics of the process of awareness of life meaning.